Validity of the Q plus question for suicide risk among general population in Nonthaburi Province, Thailand - Rortseanglum, Sontaya; Bosittipichet, Tatree; Leesri, Thanakamon (International Journal Of Community Medicine And Public Health, 2025)
Background: Suicidality is an important problem in Thailand. Currently, a Suicide risk screening questionnaire (Q plus) has been developed and tested in psychiatric patients. However, there is limited data on the general population. This study aims to determine the accuracy of the Q plus assessment and the use of Q plus in combination with the 9Q to screen for suicide risk in the general population. Data was collected during December 2022 to May 2023. Methods: Cross-sectional study (Diagnostic accuracy research) was established in this study. Data was collected using the 2Q plus 9Q 8Q evaluation form by health volunteers in the general population aged 18 to 60 years and above. Results: The sensitivity and specificity of the Q plus questions, the 9Q assessment and the combination of Q plus and 9Q were analysed. The Q plus questions showed sensitivity and specificity values of 53.13% and 97.2% respectively. These values were close to the screening by 9Q assessment with a score greater than or equal to 7 before the 8Q suicide risk assessment, which had sensitivity and specificity values of 46.88% and 94.9% respectively. It can be concluded that both assessments have low sensitivity, but using the Q plus and 9Q screening tests together increased the sensitivity to 81.25%. Conclusions: The prevalence of suicide risk in Nonthaburi Province, Thailand, was found to be 5%. The evaluating the Q plus with the 9Q when either one is positive has a sensitivity and specificity making it useful for screening suicide risk in other people.